PENERAPAN PEMBELAJARAN INKUIRI TERMBIMBING UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN KETERAMPILAN PROSES SAINS PADA MATERI CIRI-CIRI MAKHLUK HIDUP DI KELAS VII MTsN RUKOH BANDA ACEH - Salwati Salwati; Mustafa Sabri; Muhammad Ali Sarong (Universitas Islam Negeri Ar-Raniry, 2017)
An experimental study on the implementation of guided inquiry learning method to improve students’ understanding and science processing skills in the concept of characteristics of organism has been conducted at MTsN Rukoh Banda Aceh in class VII. The aims of this study were (1) to determine the understanding of the concept of characteristics of living things through the application of guided inquiry learning, (2) to find out the improvement of students’ science processing skills in the concept of characteristics of living things by using guided inquiry learning, and (3) to determine the difference of understanding enhancement of the concept among the students who get guided inquiry learning. The data were analyzed by using SPSS 16.0 for Windows. The results showed that (1) there was an improvement of understanding of the concept in the experimental class with an average value was 61.95, while the control class was 35.70 with the difference was 26.25 and (2) the observation of teachers' activities showed that the interactions of teachers and students developed better compared to conventional learning. It can be concluded that (1) there was a significant difference between the application of guided inquiry method and conventional methods to increase students 'understanding of concepts (2) there was an increasing of students’ understanding of the concept and science processing skills through the implementation of guided inquiry learning.